2015
DOI: 10.1016/j.jmarsys.2014.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting optical properties of surface waters across the Fram Strait and its potential biological implications

Abstract: Underwater light regime is controlled by distribution and optical properties of colored dissolved organic matter (CDOM) and particulate matter. The Fram Strait is a region where two contrasting water masses are found. Polar water in the East Greenland Current (EGC) and Atlantic water in the West Spitsbergen Current (WSC) differ with regards to temperature, salinity and optical properties. We present data on absorption properties of CDOM and particles across the Fram Strait (along 79°N), comparing Polar and Atl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
68
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 49 publications
(96 citation statements)
references
References 60 publications
14
68
2
Order By: Relevance
“…The influence of transformed AW generated in the Barents and Norwegian seas had impacted a CDOM (443) values in the Beaufort Gyre and Amundsen and Nansen basins, causing its decrease below 0.2 m −1 as reported by Gonçalves-Araujo et al (2018). The reported lower range of a CDOM (350) observed in AW during AREX2014 (2014: 0.14 ± 0.06 m −1 ) is in good agreement with data from the eastern part of Fram Strait at the 79 • N section reported by Granskog et al (2012), , and Pavlov et al (2015) and with data reported by Hancke et al (2014) south of the Polar Front in the Barents Sea. Kowalczuk et al (2017) observed similar a CDOM (350) values north of Svalbard.…”
Section: Variability In and Spectral Properties Of Cdom In The Nordicsupporting
confidence: 86%
See 4 more Smart Citations
“…The influence of transformed AW generated in the Barents and Norwegian seas had impacted a CDOM (443) values in the Beaufort Gyre and Amundsen and Nansen basins, causing its decrease below 0.2 m −1 as reported by Gonçalves-Araujo et al (2018). The reported lower range of a CDOM (350) observed in AW during AREX2014 (2014: 0.14 ± 0.06 m −1 ) is in good agreement with data from the eastern part of Fram Strait at the 79 • N section reported by Granskog et al (2012), , and Pavlov et al (2015) and with data reported by Hancke et al (2014) south of the Polar Front in the Barents Sea. Kowalczuk et al (2017) observed similar a CDOM (350) values north of Svalbard.…”
Section: Variability In and Spectral Properties Of Cdom In The Nordicsupporting
confidence: 86%
“…The CDOM distribution in the area influenced by AW was reported by Stedmon and Markager (2001) in the central part of the Greenland Sea, and by Granskog et al (2012) and Pavlov et al (2015), who presented CDOM and particulate absorption distribution along a transect across the Fram Strait at 79 • N. Hancke et al (2014) studied the seasonal distribution of the CDOM absorption coefficient (a CDOM (λ)) in an area across the Polar Front in the central part of the Barents Sea. Seasonal studies on CDOM contribution to overall variability in inherent optical properties (IOPs) reported on sea ice (Kowalczuk et al, 2017) and in the water column during a spring under-ice phytoplankton bloom north of Svalbard .…”
mentioning
confidence: 85%
See 3 more Smart Citations